SAT0573 Sociodemographic, clinical characteristics and joint involvement of a chikungunya epidemic in colombia. (15th June 2017) - Rueda, JC; Angarita, J-I; Santos, AM; Saldarriaga, E-L; Pelaez-Ballestas, I; Couto-Luvie, E; Londono, J
Abstract : Background: During 2014 and 2015 a chikungunya epidemic took place in Colombia concurrently with a COPCORD study across the country. Objectives: To describe the clinical characteristics of CHIKV infection in 6 different cities in Colombia and determine the most frequently associated clinical picture with CHIKV. Methods: World Health Organization criteria was used to identify CHIKV patients. A complete characterization and confirmation was established with CHIKV immunoglobulin G and IgM serology. Four possible scenarios were stablished: patients who met or not the criteria for probable case, and patients who met or not the criteria for confirmed case. P values were calculated between patients who met or not met the criteria. Sensibility and specificity was calculated for the WHO criteria. Results: A total of 604 patients with MSK symptoms were evaluated in 6 different cities. The sociodemographic, clinical characteristics and joint involvement of the studied population is depicted in tables 1 and 2. Sensibility and specificity of the WHO criteria were 56.2% and 91.1% respectively (PPV: 83.3%, NPV: 74.4%). Conclusions: Our study shows a clear clinical picture of systemic symptoms, high titters of CHIKV immunoglobulins, and a defined joint involvement, which will help clinicians to identify and differentiate CHIKV infection from other viral infections and MSK diseases. Also, the sensibility of the WHO criteria applied to our cohort of patients demonstrates the need to improve clinical criteria without the use of laboratory tests. Disclosure of Interest: None declared